Evaluation of a teaching strategy based on integration of clinical subjects, virtual autopsy, pathology museum, and digital microscopy for medical students - Julio A Diaz-Perez; Sharat Raju; Jorge H Echeverri (Elsevier, 2014)
Background: Learning pathology is fundamental for a successful medical practice. In recent years, medical education has undergone a profound transformation toward the development of an integrated curriculum incorporating both basic science and clinical material. Simultaneously, there has been a shift from a magisterial teaching approach to one centered around problem-based learning. Now-a-days, informatics tools are expected to help better implement these strategies. Aim: We applied and evaluated a new teaching method based on an active combination of clinical problems, gross pathology, histopathology, and autopsy pathology, all given through informatics tools, to teach a group of medical students at the Universidad de Santander, Colombia. Design: Ninety-four medical students were followed in two consecutive semesters. Students were randomized to receive teaching either through traditional methodology or through the new integrated approach. Results: There was no significant difference between the intervention group and the control group at baseline. At the end of the study, the scores in the intervention group were significantly higher compared to the control group (3.91/5.0 vs. 3.33/5.0, P = 0.0008). Students and tutors endorsed the benefits of the integrated approach. Participants were very satisfied with this training approach and rated the program an 8.7 out of 10, on average. Conclusion: This study confirms that an integrated curriculum utilizing informatics systems provides an excellent opportunity to associate pathology with clinical medicine early in training of medical students. This can be possible with the use of virtual microscopy and digital imaging.